REFORMATION OF THE STRUCTURE INTERNATIONAL HEALTH LAW IN ORDER TO IMPROVE THE TRANSBOUNDARY INFECTIOUS DISEASES MANAGEMENT - Aktieva Tri Tjitrawati (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The structure of international health law is currently composed under the philosofical basis of segregate and dichotomous international community. This structure affects the handling and management of TID, which is currently much harm the interests of developing countries as the emerging of multinational pharmaceutical companies. This study aimed to understand and analyse the existing system and structure of international health law (lex lata) to be used as a basis in an effort to design an ideal structure of international health law system.Keywords:international health, reform, structure of law.Key words: International health, reformation, legal structure.